Concurrent Celiac Disease, Idiopathic Thrombocytopenic Purpura and Autoimmune Thyroiditis: A Case Report - CESUR, YAŞAR; DOGAN, Murat; SAL, Ertan; Akbayram, Sinan; PEKER, Erdal; Cesur, YAŞAR; Öner, Ahmet Cihat (My University, 2011)
Celiac disease (CD) is a disease of the small intestine caused by an immune response to ingested gluten. Idiopathic thrombocytopenic purpura (ITP) is a common acquired bleeding disorder of childhood. It may follow a viral infection or immunization and is caused by an inappropriate response of the immune system. Autoimmune thyroiditis (AT) is a disease that occurs due to autoimmune mechanisms. Celiac disease associated with autoimmune thyroid disease is well known, but the association of CD, autoimmune thyroid disease, and ITP has been reported very rarely in the literature. In the current report, we have presented a case with CD, AT, and acute ITP, because this association is rarely seen, and to emphasize that CD and AT should be kept in mind in patients with ITP.